2017
DOI: 10.1371/journal.pone.0180384
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor oxidative stress in hyperoxia-induced proliferative retinopathy accelerates rd8 degeneration

Abstract: To investigate the impact of photoreceptor oxidative stress on photoreceptor degeneration in mice carrying the rd8 mutation (C57BL/6N). We compared the hyperoxia-induced proliferative retinopathy (HIPR) model in two mouse strains (C57BL/6J and C57BL/6N). Pups were exposed to 75% oxygen, starting at birth and continuing for 14 days (P14). Mice were euthanized at P14, or allowed to recover in room air for one day (P15), seven days (P21), or 14 days (P28). We quantified retinal thickness and the length of residua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…This not only extends to strains (for example, C57BL/6 vs. C3H/HeN) but also to substrains (for example, C57BL/6J vs. C57BL/6N). This is not a trivial concern, since there are demonstrable differences in the response of the retina to 75% O 2 from P1 to P14 between C57BL/6J and C57BL/6N mouse pups (268). These effects are not limited to hyperoxia, since the gut metabolome and microbiome differ between C57BL/6J and C57BL/6N mice maintained on a high-fat diet, an area of interest in lung alveolarization (554).…”
Section: Technical Concerns About Reportingmentioning
confidence: 99%
“…This not only extends to strains (for example, C57BL/6 vs. C3H/HeN) but also to substrains (for example, C57BL/6J vs. C57BL/6N). This is not a trivial concern, since there are demonstrable differences in the response of the retina to 75% O 2 from P1 to P14 between C57BL/6J and C57BL/6N mouse pups (268). These effects are not limited to hyperoxia, since the gut metabolome and microbiome differ between C57BL/6J and C57BL/6N mice maintained on a high-fat diet, an area of interest in lung alveolarization (554).…”
Section: Technical Concerns About Reportingmentioning
confidence: 99%
“…A similar strain‐dependent inflammatory response had also been noted in adult mice from six and nine inbred strains exposed to hyperoxia. These concerns extend to substrains, given demonstrable differences in responses of the retina to 75% O 2 over the period P1 to P14, comparing C57BL/6J and C57BL/6N mouse pups …”
Section: Introductionmentioning
confidence: 99%
“…Accumulating research has indicated that oxidative stress serves a crucial role in the pathogenesis of AMD (37). Oxidative stress is thought to be a major contributor to photoreceptor damage, which may eventually lead to a loss of vision (38). These processes are involved in the formation of ROS, and increasing evidence has demonstrated that oxidative stress-induced ROS production exceeds the limits of scavenging, which leads to an imbalance between the oxidative and antioxidant systems (39).…”
Section: Discussionmentioning
confidence: 99%